Restraint stress enhances arterial thrombosis in vivo – role of the sympathetic nervous system. (January 2014) - Stämpfli, Simon F.; Camici, Giovanni G.; Keller, Stephan; Rozenberg, Izabela; Arras, Margarete; Schuler, Beat; Gassmann, Max; Garcia, Irene; Lüscher, Thomas F.; Tanner, Felix C.
Abstract Stress is known to correlate with the incidence of acute myocardial infarction. However, the molecular mechanisms underlying this correlation are not known. This study was designed to assess the effect of experimental stress on arterial thrombus formation, the key event in acute myocardial infarction. Mice exposed to 20 h of restraint stress displayed an increased arterial prothrombotic potential as assessed by photochemical injury-induced time to thrombotic occlusion. This increase was prevented by chemical sympathectomy performed through 6-hydroxydopamine (6-OHDA). Blood-born tissue factor (TF) activity was enhanced by stress and this increase could be prevented by 6-OHDA treatment. Vessel wall TF, platelet count, platelet aggregation, coagulation times (PT, aPTT), fibrinolytic system (t-PA and PAI-1) and tail bleeding time remained unaltered. Telemetric analysis revealed only minor hemodynamic changes throughout the stress protocol. Plasma catecholamines remained unaffected after restraint stress. Tumor necrosis factor alpha (TNF-α) plasma levels were unchanged and inhibition of TNF-α had no effect on stress-enhanced thrombosis. These results indicate that restraint stress enhances arterial thrombosis via the sympathetic nervous system. Blood-borne TF contributes, at least in part, to the observed effect whereas vessel wall TF, platelets, circulating coagulation factors, fibrinolysis and inflammation do not appear to play a role. These findings shed new light on the understanding of stress-induced cardiovascular events.